"\\frac{dy}{3x^2}=(1+y^2)^{\\frac{3}{2}}dx\\\\\n\\Rightarrow \\frac{dy}{(1+y^2)^{\\frac{3}{2}}}=3x^2.dx"
Integrate both sides:
"\\intop \\frac{dy}{(1+y^2)^{\\frac{3}{2}}}=\\intop3x^2.dx"
Put "y=tan \\theta \\\\"
"\\therefore dy=sec^2 \\theta.d\\theta"
"\\intop \\frac{sec^2\\theta }{(1+tan^2 \\theta )^{\\frac{3}{2}}} d\\theta =x^3+c"
"\\Rightarrow \\intop \\frac{sec^2\\theta}{sec^3\\theta} d\\theta =x^3+c\\\\\n\\Rightarrow \\intop cos\\theta d\\theta=x^3+c\\\\\n\\Rightarrow sin\\theta=x^3+c\\\\\n\\Rightarrow \\frac{y}{\\sqrt{y^2+1}}=x^3+c"
Comments
Leave a comment